Prediction of clothing mobility using a musculoskeletal simulator. Issue 1 (5th November 2019) - Horiba, Yosuke; Tokutake, Ayumu; Inui, S.
Abstract : Purpose: Mobility is one of the important elements in clothing design. The purpose of this paper is to examine the predictability of clothing mobility via musculoskeletal simulation. Design/methodology/approach: In order to carry out the musculoskeletal simulation considering the influence of clothing, simulation of the dressed state was attempted. This paper simulated the dressed state and measured the motion-related deformation of the clothing to estimate the force applied to the human body based on the material property of the clothing samples. The dressed state was simulated using an external force in the musculoskeletal model. Findings: When the elbow flexion torque with an elbow supporter was calculated using the above-mentioned method of musculoskeletal simulation, it was confirmed that the lower the stretchability of the sample, the higher the elbow flexion torque. In addition, the sensory evaluation performed under the same condition as that in the simulation showed that the lower the joint torque during the motion, the higher the subjective mobility, and that the higher the joint torque, the lower the subjective mobility. Thus, it is suggested that musculoskeletal simulation of the dressed state can predict the clothing mobility. Research limitations/implications: However, the method proposed in this paper requires the measurement of the deformation of the clothing to estimate the force applied to the human body. Thus, it is difficult to apply this in the measurement of general clothing that allows enough space between it and the human body, requiring further improvement of the dressed state simulation method. Originality/value: Because it is difficult to estimate the force applied by the clothing to the human body, only a few studies have performed analysis on the effect of clothing by using musculoskeletal simulation. Conversely, although the force applied by the clothing to the human body needs to be estimated in advance by the measurement of the deformation, the utility of the simulation in clothing design seems to be high because the simulation can estimate clothing mobility and the effects of clothing on muscle activity.